Factors associated with suboptimal blood pressure control in a multi-ethnic population in Amsterdam. (30th September 2020) - van der Linden, E L; Collard, D; Beune, E J A J; Nieuwkerk, P T; Galenkamp, H; Haafkens, J A; Moll van Charante, E P; van den Born, B J H; Agyemang, C
Abstract: Background: Among patients using antihypertensives, blood pressure (BP) control is generally low and appears to vary between ethnicities. We aimed to identify factors associated with suboptimal BP control in a multi-ethnic population. Methods: Cross-sectional data of the Healthy Life in an Urban Setting (HELIUS) study were used, including participants aged 18-70 years, with Dutch, African Surinamese (AS), South-Asian Surinamese (SAS), Ghanaian, Turkish or Moroccan ethnicity living in Amsterdam, the Netherlands. Suboptimal BP control was defined as BP ≥ 140/90 mmHg among participants using antihypertensives. Logistic regression analysis was performed to identify sociodemographic, lifestyle, health and psychosocial factors associated with suboptimal BP control for the total population and for each ethnic group. Results: A total of 3, 571 participants (500 Dutch, 1052 AS, 656 SAS, 637 Ghanaian, 433 Turkish, 293 Moroccan) were included in the analysis, of whom 53.3% had suboptimal BP control. Female sex (OR 0.50, 95%CI 0.43-0.59), being married (0.83, 0.72-0.96), current smoking (0.78, 0.65-0.94), obesity (1.67, 1.35-2.06), cardiovascular disease (CVD) history (0.56, 0.46-0.68), non-adherence to antihypertensives (1.26, 1.00-1.58), and family history of hypertension (1.19, 1.02-1.38) were associated with suboptimal BP control. Among ethnic subgroups, female sex was associated with lower odds of suboptimal BP control in all ethnic groups, as was current smoking (Turkish) and CVD history (Dutch, SAS, AS), whereas obesity (Dutch, AS, Turkish), older age (Turkish) and non-adherence to antihypertensives (Dutch) were associated with higher odds of suboptimal BP control. Conclusions: Our analysis identifies several factors that are independently associated with suboptimal BP control, with only small variation between ethnic groups, suggesting that focussing on well-known determinants of suboptimal BP control is worthwhile to improve BP control rates in a multi-ethnic population. Key messages: Several factors are associated with suboptimal blood pressure control in a multi-ethnic population, with only small variation between ethnic groups. These findings suggest that focussing on well-known determinants of suboptimal BP control is worthwhile to improve BP control rates in a multi-ethnic population.